Eventos de drenagem de ar na camada limite muito estável - Maia, Pamella Olimpia Andrade (2022)
The very stable boundary layer occurs on nights with light wind and clear skies, which cause strong radiative cooling on the surface, changing the structure and some characteristics of the normal stable boundary layer. Drainage winds are a characteristic circulation of the very stable boundary layer in environments with slight inclination, they are relatively difficult to be studied due to their very small scale, which makes the flows difficult to be measured. Therefore, measured data were obtained from the 30-meter-high micrometeorological tower, located at the Federal University of Santa Maria (UFSM), in order to identify and investigate drainage events that occurred in the year 2021 in the region of Santa Maria in Rio Grande. do Sul, in order to understand its behavior and impacts on the Nocturnal Boundary Layer flows. High frequency data from the micrometeorological tower located in the city of Santa Maria-RS were used. 78 cases of drainage winds events were identified, before the drainage events it was found that there is a minimum of turbulent kinetic energy, during the drainage events the wind speed reaches its maximum in the first 5 meters of height, the wind direction predominant in these events is between 100 and 150 ◦ . As a result of mixing caused by the draining winds, there was significant vertical mixing in the first 30 meters, heating the lower levels up to 10 meters and cooling the levels above.